Implementing Centralized Waiting Lists for Patients without a Family Physician in Québec - Mylaine Breton; Jennissa Gagne; Fortuné Gankpe (Health Reform Observer - Observatoire des Réformes de Santé, 2014)
In 2008, the Québec government mandated the ninety-four Centres de Santé et des Services Sociaux (CSSS or Centres for Health and Social Services) to implement a Guichet d’Accès aux Clientèles Orphelines (GACO)—a centralized waiting list to help patients without a family physician find one. Specifically, the goal of GACOs is to increase the number of patients with a family physician as well as to give priority access to vulnerable patients. The media treatment of ‘orphan’ patients as well as the Fédération des Médecins Omnipraticiens du Québec (FMOQ or Federation of General Practitioners of Québec) both played a crucial role in the design and implementation of the reform. How the reform should be implemented was not detailed, leaving each CSSS considerable latitude in the strategies they adopted to introduce it on the ground. This room to manoeuvre led to large variability in what services GACOs offer and inequity in access to services for the population. Since their implementation, financial incentives set up to encourage the participation of family physicians have been modified twice, in particular with the goal of increasing the enrolment of more vulnerable patients through GACOs. A recent study shows that, despite a large difference in incentives to physicians for these vulnerable patients, more than 70% of patients enrolled with a family physician through a GACO are ‘non-vulnerable’ and are registered into the GACO from family physician self-referrals. Nonetheless, GACOs address an important problem by reducing the number of persons without a family physician.